POST-DISCHARGE NURSING CARE FOR CHRONIC KIDNEY DISEASE PATIENTS USING INTERACTIVE VOICE RESPONSE & WEB-BASED DECISION SYMPTOM MANAGEMENT SYSTEM: A LITERATURE REVIEW - Harin Hidayahturochmah (International Journal of Nursing and Health Services (IJNHS), 2019)
Sustainable treatment of chronic kidney disease (CKD) should include deceleration of disease development and maintain quality of life when it already on end-stage condition. Specific methods are needed for nurses to care for discharged patients efficiently. The process that currently developed the most is a communication technology-based method, and one of the potential ways is Interactive Voice Response (IVR) and Web-Based Decision Support-Symptom Management System (DS-SMS). The study aimed to describe Interactive Voice Response (IVR) and Web-Based Decision Support-Symptom Management System (DS-SMS) and its function for post-discharge nursing care for chronic kidney disease. All articles were selected through Google Sholar, ProQuest, EBSCOhost, and SpringerLink online database search were with keywords and inclusion criteria. IVR and Web-Based DS-SMS is a combination of interactive voice recording telephone systems and logical database systems that can be used for post-discharge patient care. Its activities, including symptom monitoring, self-management coaching, and nurse practitioners' follow-up. It requires sophisticated design and development of content and systems, and in its application, resource use can be minimized. This system is particularly suitable for patients with chronic kidney disease, who require symptoms management such as nausea, vomiting, changes in urine output, sleep disturbances, and pruritus, and require education and intervention such as fluid and electrolyte control. Post-discharge nursing care using IVR and Web-Based DS-SMS is the potential to be applied in CKD patients. Keywords: Chronic kidney disease, post-discharge care, IVR, web-based DS-SMS